The Effect of Providing Education About Dengue Hemorrhagic Fever (DHF) on Public Knowledge and Attitudes - Warohma Nur Hidayah; Deli Lilia; Eka Joni Yansyah; Fera Novitry (Media Informasi, 2026)
Introduction: Dengue Hemorrhagic Fever (DHF) is an environmentally based disease whose incidence can be reduced by carrying out vector control measures, namely by means of mosquito nest eradication (PSN) movements. Method: The research design used was a quasi-experimental pre-test and post-test. The population in this study, based on data from visits in April, was 105, followed by 111 in May, and 109 in June. Therefore, the average number of visits over the past three months was 108.3, or 109 people. The sample in this study was all patients who visited during the study period. Results: Based on the analysis, it is known that the mean value or average value of post-test knowledge is 8.52, which is greater than the mean value or average value of pre-test knowledge of 4.96 and the Standar. Deviation value of post-test knowledge is 1.767, which is greater than the Standar. Deviation value of pre-test knowledge of 1.046. Based on the analysis, it is known that the mean value or average value of post-test attitude is 36.20, which is greater than the mean value or average value of pre-test knowledge of 22.36 and the Standar. Deviation value of post-test knowledge is 6.689, which is greater than the Standar. Deviation value of pre-test knowledge of 3.500. Conclusion: Based on the analysis, it is known that the results of the paired t-test statistical test obtained a ρ Value of 0.000, so it can be concluded that there is an influence of counseling on the knowledge of environmental-based diseases (DBD) at the Muaradua Community Health Center UPT, South OKU Regency. The results of the paired t-test statistical test obtained a ρ Value of 0.000, so it can be concluded that there is an influence of counseling on the attitude of environmental-based diseases (DBD) at the Muaradua Community Health Center UPT, South OKU Regency.